2011
DOI: 10.1111/j.1365-2125.2010.03824.x
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin/clavulanic acid‐warfarin drug interaction: a randomized controlled trial

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Increased INR was previously observed in patients treated with warfarin and amoxicillin/clavulanic acid (amoxiclav) combination. To date, no prospective study has yet evaluated the effect of amoxiclav on INR in patients on warfarin therapy and consequently, there are no clear-cut conclusions or clear recommendations for clinicians. WHAT THIS PAPER ADDS• We provided the first systematic prospective evaluation of the interaction between amoxiclav and warfarin and found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 20 publications
(29 reference statements)
1
34
0
2
Order By: Relevance
“…. Several studies have shown that CYP expression and activity may be decreased in humans during infection or inflammation, resulting in lowered drug clearance, increased toxicity and altered physiological function 1,2) . The infection itself (inflammatory syndrome) may alter the warfarin metabolism or hepatic clotting factor synthesis 2,3) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…. Several studies have shown that CYP expression and activity may be decreased in humans during infection or inflammation, resulting in lowered drug clearance, increased toxicity and altered physiological function 1,2) . The infection itself (inflammatory syndrome) may alter the warfarin metabolism or hepatic clotting factor synthesis 2,3) .…”
Section: Discussionmentioning
confidence: 99%
“…Some case reports have suggested that macrolides have the potential to enhance the anticoagulation effect of warfarin [1][2][3] . However, no prospective study has yet evaluated the effect of AZ-ER on the anticoagulation of warfarin therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La période postopératoire est une période critique car elle s'accompagne bien souvent d'une nouvelle prescription et/ou d'une modification des habitudes alimentaires. Un suivi clinique et/ou biologique est nécessaire en cas de prescription anti-infectieuse et/ou antalgique [23,38,52,72,79,159,171,187,208,241,268,289,291,292].…”
Section: Médicaments Et Alimentationunclassified
“…Concernant la prescription d'amoxicilline seule ou en association avec l'acide clavulanique, des données contradictoires sont rapportées dans la littérature. Des cas cliniques [38,52,79,188,268], une étude cas-témoin [241], une enquête prospective [261] [292]. Il est à rappeler qu'une infection avec les modications métaboliques qui l'accompagnent est en soit un facteur de risque de déséquilibre du traitement anticoagulant oral.…”
Section: Quelles Sont Les Prescriptions Médicamenteuses Potentialisatunclassified